SOSIALISASI TATA KELOLA KEUANGAN DESA: PENDEKATAN ZONA INTEGRITAS DESA (ZIDES) - Tajuddin Tajuddin; La Ode Suriadi; Arifuddin; Sulvariani Tamburaka; Ernawati Ernawati; Anida Alimirah Syahid (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
The implementation of Law No. 6 of 2014 on Villages requires village governments to manage public finances transparently, accountably, and responsibly. However, many villages continue to face challenges in strengthening governance and preventing the misuse of village funds. To address these issues, a Community Service Program integrated with Thematic Community Service (KKN) was conducted in Amoito Village, West Ranomeeto District, South Konawe Regency, by implementing the Village Integrity Zone (ZiDes) approach. The program involved KKN students and field supervisors in a series of activities, including socialization, capacity building for village officials, mentoring, and the promotion of village innovation to improve financial governance. The program results demonstrated an increase in the knowledge and awareness of village officials regarding accountability and transparent financial management. Furthermore, the activities strengthened stakeholders' commitment to establishing an efficient, transparent, and accountable village governance system that supports sustainable village development.